Healthcare needs in elderly patients with chronic heart failure in view of a personalized blended collaborative care intervention: a cross sectional study - Gostoli, Sara; Bernardini, Francesco; Subach, Regina; Engelmann, Petra; Jaarsma, Tiny; Andréasson, Frida; Rasmussen, Sanne; Thilsing, Trine; Eilerskov, Natasja; Bordoni, Barbara; Della Riva, Diego; Urbinati, Stefano; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Few studies explored healthcare needs of elderly heart failure (HF) patients with comorbidities in view of a personalized intervention conducted by Care Managers (CM) in the framework of Blended Collaborative Care (BCC). The aims of the present study were to: (1) identify perceived healthcare needs/preferences in elderly patients with HF prior to a CM intervention; (2) investigate possible associations between healthcare needs/preferences, sociodemographic variables (age; sex) and number of comorbidities. Method Patients aged 65 years or more affected by HF with at least 2 medical comorbidities were enrolled in the study. They were assessed by structured interviewing with colored cue cards that represented six main topics including education, individual tailoring of treatment, monitoring, support, coordination, and communication, related to healthcare needs and preferences. Results Thirty-three patients (Italy = 21, Denmark = 7, Germany = 5; mean age = 75.2 ± 7.7 years; males 63.6%) were enrolled from June 2021 to February 2022. Major identified needs included: HF information (education), patients' involvement in treatment-related management (individual tailoring of treatment), regular checks of HF symptoms (monitoring), general practitioner update by a CM about progression of symptoms and health behaviors (coordination), and telephone contacts with the CM (communication). Regarding communication modalities with a CM, males preferred phone calls (χ2 = 6.291, p = 0.043) and mobile messaging services (χ2 = 9.647, p = 0.008), whereas females preferred in-person meetings and a patient dashboard. No differences in needs and preferences according to age and number of comorbidities were found. Discussion The findings highlight specific healthcare needs and preferences in older HF multimorbid patients, allowing a more personalized intervention delivered by CM in the framework of BCC.